2010
DOI: 10.1039/b915652f
|View full text |Cite
|
Sign up to set email alerts
|

Redox and complexation chemistry of the CrVI/CrV/CrIV-d-glucuronic acid system

Abstract: When excess uronic acid over Cr(VI) is used, the oxidation of D-glucuronic acid (Glucur) by Cr(VI) yields D-glucaric acid (Glucar) and Cr(III) as final products. The redox reaction involves the formation of intermediate Cr(IV) and Cr(V) species, with Cr(VI) and Cr(V) reacting with Glucur at comparable rates. The rate of disappearance of Cr(VI), and Cr(V) increases with [H(+)] and [substrate]. The experimental results indicated that Cr(IV) is a very reactive intermediate since its disappearance rate is much fas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 54 publications
3
15
0
Order By: Relevance
“…The intensity ratio between the absorption bands at 245 and 290 nm was 2.2, which conrmed . 18,55,56,63 As occurred with other substrates studied previously, 18,[25][26][27]37 the monotonic growth at 290 nm was found to follow rst-order kinetics (Fig. 6B).…”
Section: Rate Studiessupporting
confidence: 83%
See 3 more Smart Citations
“…The intensity ratio between the absorption bands at 245 and 290 nm was 2.2, which conrmed . 18,55,56,63 As occurred with other substrates studied previously, 18,[25][26][27]37 the monotonic growth at 290 nm was found to follow rst-order kinetics (Fig. 6B).…”
Section: Rate Studiessupporting
confidence: 83%
“…The UV-vis absorption spectrum of the QA/Cr VI reaction mixture in an acidic medium (HClO 4 ) showed the characteristic behavior of Cr VI in an acidic medium [25][26][27] with a shoulder at 420/450 nm and a band at 350 nm (Fig. 2).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Most of all, DLA is water soluble and possesses negatively charged carboxyl groups, which might electrostatically interact with Ag + and promote the distribution of Ag + in the cellulose matrix [36,37]. It also has been reported that DLA was able to reduce Cr +5 to Cr +3 [38]. From this point, we can except that the DLA can also be used to reduce silver ions to AgNPs on cellulose fibers.…”
Section: Introductionmentioning
confidence: 93%